KONSTRUK KOMPETENSI LITERASI UNTUK SISWA SEKOLAH DASAR - Tadkiroatun Musfiroh; Beniati Listyorini (LITERA, 2016)
This study aims to: (1) describe the literacy components based on the PIRLS version,  (2) identify the constructs of reading literacy competence for Grade IV of the elementaryschool, and (3) make a draft of the constructs of literacy competence for Grade IV of theelementary school in the Indonesian version. The data were collected through literaturereview, interviews, and focus group discussion. They were analyzed by the qualitativedescriptive technique. The results are as follows. First, the literacy components basedon the PIRLS version comprise: the reading literacy concept, assessment framework,benchmark, literary text components, and assessment system determination. Second, thereading literacy competence is constructed as the competence to read and comprehendliterary and informative texts, based on four cognitive levels, from a variety of text typesin line with the social context around the students and the national context. Third, theconstructs of literacy competence in the Indonesian version consist of: 2-5 difficult words,a text length of 200 words, the composition of low to high cognitive levels of 30-30-3010,textthemessuitabletoIndonesianconditionandculture,cleartextillustrations,andtables/graphspresentedingradation.Theresultsareimportantasliteracyinformationforthe basis for developingeducational policies in Indonesia.